A Traditional Costa Rican Adolescents' Diet Score Is a Valid Tool to Capture Diet Quality and Identify Sociodemographic Groups With Suboptimal Diet - Monge-Rojas, Rafael; O'Neill, June; Lee-Bravatti, Michelle; Mattei, Josiemer (Frontiers in Public Health, 2021)
Traditional diet indices may capture diet quality according to local food culture. Higher adherence to traditional diet scores may help prevent disease, yet evidence in adolescents is limited. This cross-sectional study aimed to develop and validate a Traditional Costa Rica Adolescents Diet Score (TCRAD) and determine its association with sociodemographic characteristics, under the hypothesis that girls, adolescents from rural areas, and with low socioeconomic status, have a more traditional healthy diet. A total of 804 urban and rural adolescents (13-18 years old) participated in the study. The TCRAD showed adequate internal validity as shown by significant associations with intake of 14 traditional foods and nutrients (legumes, vegetables, fruits, oils, dairy, and corn tortilla scored as healthy; and white rice, red/processed meat, fats, desserts/pastries, sugar-sweetened beverages, snacks, fast food, and bread and cookies scored as unhealthy). A high TCRAD score, indicative of a healthier and more traditional diet, was observed among adolescents in the low socioeconomic group vs. medium or high socioeconomic categories (42.9%, 41.2% and 38.2% respectively, p<0.05), adolescents living in rural areas vs. urban (47.6% vs. 34.2%, p<0.05), and among boys vs. girls (46.9% vs. 37.5%, p<0.05). The TCRAD score is a valid tool to capture diet quality of adolescents in Costa Rica and could be used to measure association of diet with disease outcomes in this and similar populations. Public health nutrition programs in Costa Rica should focus on improving intake of foods and nutrients, and prioritize girls, adolescents in urban areas, and adolescents with high socioeconomic status